Keynote Speaker to Participant Interaction in Online Webinar by Using Zoom Application - Dani, Ersika Puspita; Agustin, Angel; Deani, Eliza (Journal of Community Research and Service, 2023)
The objective of this descriptive qualitative study was to find out the keynote speaker to participant in online webinar by using zoom application. A keynote speaker has been conducted as a participant. To examine keynote speaker to participant, observation in zoom application were be used. The observation was be used to find out the keynote speaker™s interaction to participant. Then, the results were be analyzed to identify form of keynote speaker™s interaction. The results were 1) There were 3 forms of interaction used by keynote speaker to participant in online webinar, namely initiation move (I-Move), response move (R-Move), and Feedback Move (F-Move), and 2) The Initiation move (I-Move) was the most dominant interaction form used by keynote speaker to participant in online webinar and the least form was feedback move (F-Move).